Analisis Kinerja Karyawan terhadap Strategi Pemasaran Motor Honda pada Dealer Argo Motor Honda Sridadi - Niki Kosasih; Irfan Widyanto; Lisa Putriyani (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
The purpose of this study is (1) to determine the performance of the employees of the Argo Motor Honda Sridadi Dealer. (2) To determine the marketing strategy of Honda Motor at Dealer Argo Honda Sridadi. (3) To analyze the employee's performance on the marketing strategy of Honda motorcycles at the Argoo Honda Sridadi Motorcycle Dealer. Descriptive quantitative and qualitative research methods are data collection methods using interviews, observations and questionnaires with a sample of 35 respondents and data analysis tools using a Likert scale. The results showed descriptively based on the results of the questionnaire, it can be concluded that the performance variable of the Argo Motor Honda Sridadi Dealer employee with a total index of 29.4 and an average index value of 2.94 and is in the scale range of 2.6 < x < 3.4 with the classification of descriptive analysis is Good Enough (CB), meaning that the respondents' responses, namely consumers descriptively agree with the indicators of work quality, work quantity, implementation of duties and responsibilities imposed by the company on all employees. based on the results of the questionnaire on the marketing strategy variable with an index of 30.4 and an average index value of 3.8 and in the range of a scale of 3.4 < x < 4.2 with a descriptive analysis classification of Good (B), meaning that the respondents' responses are descriptively, consumers agree with the marketing strategy carried out by the Argo Motor Honda Sridadi Dealer.